GENETIC INTERFERENCE WITH PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR γ IN SMOOTH MUSCLE ENHANCES MYOGENIC TONE IN THE CEREBROVASCULATURE VIA A RHO KINASE-DEPENDENT MECHANISM - De Silva, T. Michael (Hypertension, 2014)
Myogenic responses by resistance vessels are a key component of autoregulation in brain, thus playing a crucial role in regulating cerebral blood flow and protecting the blood-brain barrier against potentially detrimental elevations in blood pressure. Although cerebrovascular disease is often accompanied by alterations in myogenic responses, mechanisms that control these changes are poorly understood. Peroxisome proliferator-activated receptor γ (PPARγ) has emerged as a regulator of vascular tone. We hypothesized that interference with PPARγ in smooth muscle would augment myogenic responses in cerebral arteries. We studied transgenic mice expressing a dominant negative mutation in PPARγ selectively in smooth muscle (S-P467L) and nontransgenic littermates (non-Tg). Myogenic tone in middle cerebral arteries (MCA) from S-P467L was elevated 3-fold compared with non-Tg. Rho kinase is thought to play a major role in cerebrovascular disease. The Rho kinase inhibitor, Y-27632, abolished augmented myogenic tone in MCA from S-P467L mice. CN-03, which modifies RhoA making it constitutively active, elevated myogenic tone to ~60% in both strains, via a Y-27632-dependent mechanism. Large conductance Ca(2+)-activated K(+) channels (BK(Ca)) modulate myogenic tone. Inhibitors of BK(Ca) caused greater constriction in MCA from non-Tg compared with S-P467L. Expression of RhoA or Rho kinase-I/II protein was similar in cerebral arteries from S-P467L mice. Overall, the data suggest that PPARγ in smooth muscle normally inhibits Rho kinase and promotes BK(Ca) function, thus influencing myogenic tone in resistance arteries in brain. These findings have implications for mechanisms that underlie large and small vessel disease in brain as well as regulation of cerebral blood flow.